The effect of NADP on some values of the renal acid-regulating function at experimental diabetes melli - Grytsiuk, M. I. (Journal of Education, Health and Sport, 2017)
Diabetes is a significant social problem, since it leads both to disability and high mortality rate. The experiment involved 32 sexually mature nonlinear males of white rats. Experimental groups of animals were administered a single streptozotocin dose of 70 mg/kg intraperitoneally and NADP – 30 mg/kg. The animals in the experimental groups were slaughtered and studied on the 11th, 21st and 31st days after streptozotocin administration. The studies have shown that NADP affects the metabolism, reduces the production of acids and, as a result, reduces the excretion of acids by the kidneys in experimental animals.